Pseudocyesis: From Psycho-Social Conflict to Somatic Reality, A Literature Review - Athalia, Ihza Namira; Yuar, Alana Akmal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pseudocyesis or pseudopregnancy is a psychosomatic condition that can occur in certain extreme situations when mental anguish, neuroendocrine malfunction, and social stress intersect. Pseudocyesis is often associated with affective disorders such as major depressive disorder, which can modulate the activity of the hypothalamic-pituitary-ovarian axis. This literature review aims to comprehensively discuss the basic concept of pseudocyesis, its etiology and pathophysiology, its relationship to depression and socio-cultural factors, and highlight the importance of a multidisciplinary approach to diagnosis and management in understanding this phenomenon as a complex biopsychosocial disorder. This article was written using the Literature Review method and compiled with the PRISMA approach. Pseudocyesis is still reported to be quite common in developing countries, particularly in rural communities in Africa and Asia. Pseudocyesis occurs due to several factors, including psychological and hormonal, as well as social and cultural factors. The pathophysiology of pseudocyesis lies in dysregulation of the Hypothalamic-Pituitary-Ovarian (HPO) axis, which is the primary control system for the female reproductive cycle. Women with pseudocyesis exhibit an endocrine profile that shares many similarities with Polycystic Ovarian Syndrome (PCOS) and Major Depressive Disorder. The most commonly reported symptoms include menstrual disorders such as amenorrhea (cessation of menstruation) or oligomenorrhea (irregular menstrual cycles), morning sickness, vomiting, and weight gain. Pseudocyesis can be managed through a combination of supportive psychotherapy, cognitive-behavioral therapy (CBT), and psychoanalytic therapy. Furthermore, family involvement, especially the partner, in the therapy process plays a vital role.